Tradition and innovation: woodcarvers at the confluence of the Umzinyathi and Umngeni rivers, KwaZulu-Natal, South Africa - Jolles, F. (Southern African Humanities, 2021)
This paper is a review of a collection of 185 items now housed in the Natal Museum, Pietermaritzburg. It consists of the principal wooden objects found in Zulu households: headrests, platters for serving meat, milking pails and spoons of various descriptions. The period covered is from the beginning of the twentieth century through to the 1990s - three generations of carvers. For each item, the owner was established and the item attributed as far as possible to its carver. Where feasible, the carvers or their descendants were interviewed, and their biographical background, opinions about their trade, assessment of their colleagues' work and other pertinent information were recorded. In spite of the limited area and the fact that many of the carvers knew of each other's work there was a surprising variation in styles of headrests and meat platters (but not milking pails). Within the array of styles the Umzinyathi River seemed to serve as a boundary, even though it is easily fordable. As a result it is possible to trace the formation of autonomous regional styles on each side of the river: for meat platters on the eastern, and for headrests on the western side.